Anticancer Potential of Cyanidin and Cyanidin-3-Glucoside Through TrkB Receptor Inhibition: Evidence From Molecular Interaction Docking - Kurnianingsih, Nia; Suprapto, Ratih Paramita; Ratnawati, Retty (JSMARTech: Journal of Smart Bioprospecting and Technology, 2024)
Cancer remains a global health problem with persisten demand on therapeutic development to inhibit cancer cells growth without harmful effects on healthy cells. Plant bioactive compounds are intensively studied as anticancer via several signalling pathway. Anticancer therapy via inhibition of tropomyosin kinase receptor-B (TrkB) signal was previously proposed as target therapy. The role of plant metabolites cyanidin and cyanidin-3-glucoside as TrkB inhibitor is has not been investigated. This study was aimed to identify physicochemical of cyanidin and cyanidin-3-glucoside as well as determine it’s role towards TrkB receptor signalling pathway through in silico approach. Molecular docking was performed using Hex 8.0.0 software and visualizes using Discovery Studio Visualizer. The energy binding of TrkB with cyanidin and cyanidin-3-glucoside was -263,21 kcal/mol and 281,65 kcal/mol respectively. Complex of cyanidin-3-glucoside had hydrogen and hydrophobic bond more than TrkB-cyanidin complex. The hydrogen bond formed at Lys637, Arg558 and Gly 561 amino residues. Physicochemical analysis demonstrated that both ligand are potential as kinase enzyme inhibitor. Cyanidin-3-glucoside was predicted more potential as anticancer than cyanidin via TrkB receptor inhibition. Future studies are required to confirm current finding both in-vitro and in-vivo models.